Answer:
![\sf A . \sf \frac{3}{-7}](https://tex.z-dn.net/?f=%5Csf%20A%20.%20%5Csf%20%5Cfrac%7B3%7D%7B-7%7D)
![\sf E. \sf -( \frac{-3}{-7} )](https://tex.z-dn.net/?f=%5Csf%20E.%20%5Csf%20-%28%20%5Cfrac%7B-3%7D%7B-7%7D%20%29)
This above options makes the expression true.
- The negatives above can be distributed up as well, which happened in A.
- In E, when the negatives inside the bracket cancels out, the negative outside the brackets multiplies and makes the expression true.
- In B the expression turns positive, thus false same happens with C and D
Answer:
R180
Step-by-step explanation:
Adjusted income = (original pocket money x new ratio) / old ratio
( 6 x $150) / 5 = $180
Answer: 7(3m - 7n)
<u>Step-by-step explanation:</u>
Factor each term then see what value(s) they have in common:
21m - 49n
∧ ∧
3 · 7 · m 7 · 7 · n
Both terms have a 7 in common. What is left over after removing the 7?
21m: 7(3m)
49n: 7(7n)
GCF: 7 Leftovers: 3m <em>and</em> 7n
Factored form of expression is: 7(3m - 7n)
Answer:
![y=2e^{sin(x)}](https://tex.z-dn.net/?f=y%3D2e%5E%7Bsin%28x%29%7D)
Step-by-step explanation:
Given equation can be re written as
............(i)
Now it is given that y(π/2) = 2e
Applying value in (i) we get
ln(2e) = sin(π/2) + c
=> ln(2) + ln(e) = 1+c
=> ln(2) + 1 = 1 + c
=> c = ln(2)
Thus equation (i) becomes
ln(y) = sin(x) + ln(2)
ln(y) - ln(2) = sin(x)
ln(y/2) = sin(x)
![y= 2e^{sinx}](https://tex.z-dn.net/?f=y%3D%202e%5E%7Bsinx%7D)